Acoustical investigations of the effect of additives on the elastic properties of raw kaolin - RYLL-NARDZEWSKA, Ewa; RYLL-NARDZEWSKI, Jan; KULIK, Andrzej; PIECZAROWSKI, Henryk (Archives of Acoustics, 1979)
To improve the mechanical strength of ceramic bodies various modifying agents are added in the raw state. The effect of the modifiers on the elastic properties of kaolin samples in the raw state and after firing was studied by acoustical methods: a resonance one and a pulse one. The results of the Young's modulus measurements obtained by the acoustical methods agree with the results obtained by other methods. The resonance methods have been found to be applicable for the examination of raw ceramic materials.